Augustine's Doctrine of the Totus Christus: Reflecting on the Church as Sacrament of Unity - Baker, Kimberly Faye (Horizons, 2010)
This article examines Augustine's doctrine of the totus Christus, "the whole Christ" with Christ as Head and the Church as Body. It considers the new identity as Christ that Christians receive in the sacraments of initiation that unite individuals in the Church community, and the sacramental presence of the Church in the world as one of unifying love. This new identity forms the Church for mission as it joins Christ in a mission of love that unites people to one another as it unites them to God. The Church joins Christ in standing in solidarity with those in need, thus radiating Christ's unifying, transformative love in the world. The article ends with a suggestion that Augustine's view of the totus Christus might be a valuable resource for delving more deeply into Vatican II's vision of the sacramental unity of the Church.